Fallas del Gobierno en el desarrollo - O. Krueger, Anne (2023)
The view of development economists in past decades was that government should play an active role in economic development, particularly when dealing with market failures. Nevertheless, government failures must be acknowledged, and government inter vention should occur only when market failures take place and when the government has a clear plan and a set of rules for its involvement. Anne O. Krueger presents some important lessons by elaborating on four questions. (1) What is the government? (2) What is the government’s comparative advantage? (3) What are the dynamics of government intervention? (4) Can a positive theory of political behavior be formulated so that it will help explain when and how alternative policies will evolve in the political are na? These answers are preliminary, and more research on the relation between political and economic markets is needed.